2020
DOI: 10.3389/fchem.2020.00272
|View full text |Cite
|
Sign up to set email alerts
|

Model Protective Films on Cu-Zn Alloys Simulating the Inner Surfaces of Historical Brass Wind Instruments by EIS and XPS

Abstract: The present work focuses on the characterization of brass surfaces after contact with artificial saliva solution at pH 7.4 and phosphate buffer solution at pH 7 simulating two extreme conditions that might occur when playing ancient brass wind instruments in the context of historically informed performance practice. The composition and the morphology of the film formed following the contact with the solutions for 1, 3, and 16 h were investigated by ex situ X-ray photoelectron spectroscopy (XPS) and scanning el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…The study of the structural features gave access to the manufacturing processes, to identifying the damages, the presence of some reparations or restorations. Even the alterations commonly found on the inner surface of tubes caused by the playing were put into evidence [23]. RX investigation suggested that the inv.878 (Figure 1c) was characterized by a lamina with a uniform thickness joint by a nipped tooth joint between the edges (Figure 2a).…”
Section: Resultsmentioning
confidence: 98%
“…The study of the structural features gave access to the manufacturing processes, to identifying the damages, the presence of some reparations or restorations. Even the alterations commonly found on the inner surface of tubes caused by the playing were put into evidence [23]. RX investigation suggested that the inv.878 (Figure 1c) was characterized by a lamina with a uniform thickness joint by a nipped tooth joint between the edges (Figure 2a).…”
Section: Resultsmentioning
confidence: 98%
“…The exponential increase of Rp with the OCP (straight line in the log Rp vs. OCP diagram) is similar for all the model solutions here examined, and also for the Tani-Zucchi solution studied in previous works. [2][3][4][5][6] The values measured for short immersion times F I G U R E 4 Diagram log Rp versus OCP for CuZn37 alloy exposed for 1, 3, and 16 h to Darvell, Carter-Brugirard, and SALMO. For comparison, the results previously obtained with Tani-Zucchi saliva [2,3] are also reported.…”
Section: Dissolution Mechanismmentioning
confidence: 99%
“…Model solutions of human saliva are used for investigating the corrosion behavior of various materials from steels to brass alloys in a wide range of applications, which includes orthodontics and cultural heritage. [1][2][3][4][5][6] The use of model solutions is required since the natural saliva is a complex mixture of organic and inorganic compounds, strongly variable from person to person as its composition depends on environmental, physiological, and pathological factors. [7][8][9][10][11][12] In addition, its composition changes throughout the day and, due to its instability outside the oral cavity, it is not usually used for in vivo and in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations